2023
DOI: 10.3390/su15065331
|View full text |Cite
|
Sign up to set email alerts
|

Power of Social Media Marketing: How Perceived Value Mediates the Impact on Restaurant Followers’ Purchase Intention, Willingness to Pay a Premium Price, and E-WoM?

Abstract: The introduction of social media in the restaurant sector has changed the manner in which customers communicate with businesses. Social media marketing activities (SMMAs), such as customization, entertainment, trendiness, and interaction may have a substantial impact on followers’ perceived value and consumer behavioral intentions. Therefore, this research aims to investigate the impact of SMMAs on restaurant social media followers’ purchase intentions (PUR), willingness to pay a premium price (WPP), and e-WoM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 84 publications
1
16
0
1
Order By: Relevance
“…They also found that these visitors influence the level and attempt to interact with other customers through WOM. In the age of communication, where technology has advanced, electronic word-of-mouth (e-WOM) communication, primarily realized by consumers sharing their experiences with other consumers and consumer candidates through various internet platforms, is also intensely alive, and people of all ages can favor it (Bushara et al , 2023). The study focuses on measuring WOM communication, one of the traditional marketing techniques, and the intention of consumers who experience local flavors to share their experiences with their immediate environment, even though e-WOM is a variable that can be evaluated within the scope of this study.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…They also found that these visitors influence the level and attempt to interact with other customers through WOM. In the age of communication, where technology has advanced, electronic word-of-mouth (e-WOM) communication, primarily realized by consumers sharing their experiences with other consumers and consumer candidates through various internet platforms, is also intensely alive, and people of all ages can favor it (Bushara et al , 2023). The study focuses on measuring WOM communication, one of the traditional marketing techniques, and the intention of consumers who experience local flavors to share their experiences with their immediate environment, even though e-WOM is a variable that can be evaluated within the scope of this study.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…In the fast-food restaurant context, food quality, as well as reasonable price, significantly affected PI [53]. In the SMM setting, advertising and brand reputation can also affect consumer purchase intention [16,17,54]. If a company has created an effective ad campaign that draws in customers, those who have seen the advertisement will likely be more inclined to consider buying the product.…”
Section: Purchase Intention (Pi)mentioning
confidence: 99%
“…Social media marketing activities can have a significant impact on sustainable purchasing intentions in several ways [16,60]. First, these activities can be used to promote sustainable products and practices, raising consumer awareness and interest in these issues.…”
Section: The Impact Of Smmas On Pimentioning
confidence: 99%
See 2 more Smart Citations